Electrochemical Preparation of Ni-La Alloy Films from N-butyl-N-Methyl Pyrrolidinium Dicyanamide Ionic Liquid as Electrocatalysts for Hydrogen Evolution Reaction. Issue 12 (1st January 2017) - Gao, M. Y.; Yang, C.; Zhang, Q. B.; Zeng, J. R.; Li, X. T.; Hua, Y. X.; Xu, C. Y.; Li, Y.
Abstract : Nickel alloys are burgeoning as interesting non-precious electrocatalysts for their excellent catalytic activity toward hydrogen evolution reaction (HER). In this work, we report a facile electrochemical strategy for fabricating porous nanoparticle-packed Ni-La alloy films grown on copper substrate from N-butyl-N-methyl pyrrolidinium dicyanamide ionic liquid (BMP-DCA IL) containing anhydrous NiCl2 and LaCl3, which can be acted as efficient and stable catalysts for HER in alkaline solution. The relevant voltammetric behaviors of Ni(II), La(III) and their mixtures in the BMP-DCA IL, potentiostatic electrodeposition processes, as well as the HER electrocatalytic performances of the resultant deposits were investigated. The electrocrystalization of Ni nuclei was found to promote the electrochemical reduction of La, and induce the co-deposition of amorphous Ni-La alloy. The prepared Ni-La alloy films coated on a copper wire (Ni-La/Cu) obtained at optimal preparing conditions exhibit high-performance HER catalytic activity with a Tafel slope of 75.6 mV dec −1 and an exchange current density of 0.115 mA cm −2 . Compared with other Ni-RE (rare earth) based HER electrocatalysts in alkaline media, the electrode needs low overpotentials of −190, −218 and −270 mV to drive cathodic current densities of 10, 20 and 100 mA cm −2, respectively, and its catalytic activity can be maintained for at least 27 h.